Экспресс-методы определения смертности яиц червеца Комстока после фумигации - Нагорная, И.М. (Вестник зоологии, 1981)
A proximate method is developed to determine the death of Pseudococcus comstocki K u w. diapausing eggs after fumigation with methyl bromide.The method is based on the presence of amylolytic activity in living eggs and its absence in dead ones. The eggs are differentiated into living and dead ones according to changes in the incubation medium colouration. During incubation amylase of living e g g s hydrolyzes the medium starch, after which addition of the iodine reagent causes yellow, colouration.During incubation of dead eggs starch is not hydrolyzed therefore addition of the iodine reagent causes violet-blue colouration of the medium. The suggested method highly reduces the time taken for determining the eggs death as compared with thecommonly used method. In case of nondiapausing eggs the death may be determined by the method based on the activity of living egg lysozyme.